Colored Petri Nets: A Graphical Language for Formal Modeling and Validation of Concurrent Systems. - JENSEN, KURT; KRISTENSEN, LARS M. (Communications of the ACM, 2015)
The article discusses Colored Petri Nets (CPNs), which combine the mathematical modeling languages known as Petri Nets with a programming language in order to provide a scalable modeling language for use in concurrent systems. Particular focus is given to the core syntactical and semantical constructs of CPNs and to the validation of CPNs' quantitative and qualitative behavioral properties through simulation-based performance analysis. Other topics include state-space exploration and software-tool support for the use of CPNs.